Awareness of and preference for disease prognosis and participation in treatment decisions among advanced cancer patients in Myanmar: Results from the APPROACH study. Issue 1 (13th September 2020) - Wynn Mon, Ssu; Myint Zu, Wah Wah; Myint Maw, Myo; Win, Han; Zin Thant, Kyaw; Yang, Grace; Malhotra, Chetna; Teo, Irene; Finkelstein, Eric; Ozdemir, Semra
Abstract: Aim: To investigate prognostic awareness, preference for prognostic information, and perceived and preferred roles in decision making among patients with advanced cancer in Myanmar. Methods: A cross‐sectional survey was administered at the Yangon General Hospital to stage 4 cancer patients who were at least 21 years old and aware of their cancer diagnosis. Patients were asked questions about their prognosis, participation in treatment decisions, sociodemographic and clinical information. Data from 131 patients were analyzed using descriptive statistics and logistic regressions. Results: Only 15% of patients surveyed were aware that their cancer was advanced and only a quarter (26%) of patients knew that treatment intent was noncurative. The likelihood of treatment‐intent awareness was higher among patients who were male, high income, and aware that they had advanced cancer. Roughly 60% of patients reported playing an active or collaborative role in treatment decisions, with a strong preference (59%) for the latter. For the majority of patients (69%), perceived and preferred roles in decision making were the same. Sociodemographic characteristics did not predict perceived and preferred roles in decision making. Conclusions: This is the first effort to analyze prognostic awareness and decision‐making practices among advanced cancer patients in Myanmar. Patients had inadequate knowledge on their disease progression and intent of treatment. Yet, the majority of them were keen to be involved in treatment decisions.